THE RELATIONSHIP BETWEEN PRINCIPALS’ SENSE OF HUMOUR AND ORGANIZATIONAL JUSTICE - Yalçın MUTLUAY (Fırat University, 2019)
The aim of this study is to state the views of the teachers about the relationship between the styles of humor by school managers and organizational justice perceptions. The nature of the study is comprised of total 2830 teachers who work at the state schools in Kahramanmaraş city centre in 2015 - 2016 academic year; the sample of the study is comprised of 265 teachers identified by “random neutral sampling” method. This research is a quantitative and descriptive. For data collection, “The Humor Styles Questionnaire” and “Organizational Justice Inventory” have been used. According to the findings, there are meaningful and positive relationship between the styles of humor by managers and distributive justice, procedural justice, independent variable which is organizational justice perception of teachers variables. Besides, in the regression analysis, medium-level significant relationships were found between all sub dimensions of organizational justice and the styles of humor by managers. According to this, the manager’s styles of humor are determinant of organizational justice perception.